Do 2-coordinate iodine(i) and silver(i) complexes form nucleophilic iodonium interactions (NIIs) in solution?. Issue 32 (11th April 2022) - Wilcox, Scott; Sethio, Daniel; Ward, Jas S.; Frontera, Antonio; Lindh, Roland; Rissanen, Kari; Erdélyi, Máté
Abstract : The interaction of a [bis(pyridine)iodine(i )] + cation with a [bis(pyridine)silver(i )] + cation, in which an iodonium ion acts as a nucleophile by transferring electron density to the silver(i ) cation, is reinvestigated herein. Abstract : The interaction of a [bis(pyridine)iodine(i )] + cation with a [bis(pyridine)silver(i )] + cation, in which an iodonium ion acts as a nucleophile by transferring electron density to the silver(i ) cation, is reinvestigated herein. No measurable interaction is observed between the cationic species in solution by NMR; DFT reveals that if there is an attractive interaction between these complexes in solution, it is dominantly the π–π interaction of pyridines.